The political economy of inequality in rich democracies - Jonathan Rothwell (Luxembourg Income Study (LIS), 2019)
Rich democracies have experienced a large increase in income inequality starting around 1980, coinciding with a rise in international trade and information technology. The leading theories used to explain changes in the income distribution - skilled biased technological change and globalization - have not been called upon to explain why the United States has been more unequal than other democracies even before the recent rise, suggesting other forces are at work. I set out to investigate those forces. First, I clarify the trends in income within the United States. The key rise occurred from 1980 to 2000 in labor income and benefited not just the top 0.1% or even the top 1% but the top 10%. Then, I explore the international correlations using both survey and tax-based sources. Greater exposure to innovation and trade does not predict higher inequality in levels of changes across rich democracies. Political economy relationships are much more successful in explaining the variation, though traditional measures of bias toward capital have mixed results. The strongest predictors of inequality are two variables: an index of excess earnings accruing to elite professionals and racial diversity. Simple regressions confirm this evidence. Digging deeper, I show that the top 1% by income or wealth are disproportionately found in domestic sectors that are not particularly innovative or affected by globalization. This is especially true for the most unequal countries. In the United States, financial sector workers, doctors, and lawyers play a large role in income inequality and are notable for their high levels of sector and occupation-specific regulations. The origins of racial inequality in the United States are well known and reviewed here. I conclude that political economy considerations must be brought into any comprehensive theory of the income distribution in the early 21st century democracies.
Keywords: 330